Impact of Work Environment, Discipline, and Motivation on Honorary Staff Performance at Surabaya Maritime Polytechnic - Damayanti, Elok; Sukoco, Agus; Rosyid, Amrun; Wulandari, Ani; Ashari, Ayu Christine (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
Purpose: This study aims to analyze the influence of work environment, work discipline, and work motivation on the performance of Honorary Staff at Surabaya Maritime Polytechnic. It examines the extent to which these factors affect performance individually and collectively. Design/methodology/approach: This research employs a quantitative approach using a survey method. The study population consists of 100 Honorary Staff at Surabaya Maritime Polytechnic, with a sample of 80 individuals selected using the Slovin formula at a 5% significance level. The sampling technique applied is simple random sampling. Data were collected through questionnaires and analyzed using multiple linear regression. Findings: Partial tests reveal that the work environment does not significantly affect employee performance, whereas work discipline and work motivation have a positive and significant impact on performance. Simultaneous tests indicate that work environment, work discipline, and work motivation collectively have a significant influence on employee performance. Research limitations/implications: This study is limited to a single institution, making it less generalizable to other sectors or organizations. Additionally, it only considers three independent variables, leaving other potential performance-influencing factors unanalyzed. Practical implications: The findings highlight the importance of work discipline and motivation in enhancing employee performance. Although the work environment does not have a direct impact, it may still play a role when interacting with other variables. Originality/value: This research contributes to understanding the key factors influencing the performance of Honorary Staff in the maritime education sector, an area that remains underexplored. Paper type: Research paper.